ANALYSIS OF WEST JAVA PROVINCE GOVERNMENT REGIONAL REVENUE BUDGET REALIZATION DURING THE PANDEMIC AND AFTER THE PANDEMIC 2020-2023 - Tommy Kuncara; Rini Dwiastutiningsih; Poso Nugroho; Bayu Nurdiansyah (Asosiasi Dosen Muda Indonesia, 2024)
The aim of this research is to analyze the Regional Revenue and Expenditure Budget (APBD) of the West Java Provincial Government during the COVID-19 pandemic period and after the pandemic, namely 2020, 2021, 2022 and 2023. This analysis is to understand how the pandemic affects regional financial management and strategies -the strategy implemented by the West Java Provincial Government in facing global economic challenges. This study uses descriptive quantitative methods with secondary data analysis obtained from the financial reports of the West Java Provincial Government. The data analyzed includes the ratio of independence, effectiveness and efficiency. This research also involves comparing financial ratios from year to year to identify patterns of change and the factors that influence them. This research aims to understand how the pandemic has an impact on income, budget expenditure and the deficit of West Java Province in the 2020-2023 period. It is hoped that the results of this research can be a reference for local governments in adopting effective policies to maintain financial stability and support sustainable economic recovery.